Comparative rotational stability of single-piece open-loop acrylic and plate-haptic silicone toric intraocular lenses - Chang, David F (Journal of cataract and refractive surgery, 2008)
To prospectively compare the early rotational stability of AcrySof SN60T toric intraocular lenses (IOLs) with that in a retrospective series of AA4203 toric IOLs. Private practice, Los Altos, California, USA. One hundred consecutive eyes with an AcrySof SN60T(3, 4, or 5) toric IOL were compared with a consecutive series of 90 AA4203 (TL or TF) toric IOLs. The same surgeon performed all IOL implantations using an identical surgical technique. In addition to deviation from the desired axis, the change in refractive cylinder was measured 1 month postoperatively. Although surgery was performed during different time periods, the 2 populations had a similar distribution of patient age, axial lengths, and spherical IOL powers. In the AcrySof SN60T group, 90%, 99%, and 100% of the IOLs were aligned at or within 5, 10, and 15 degrees, respectively, of the desired axis and in the AA4203 group, 70%, 90%, and 97%, respectively. The mean IOL rotation was 5.56 degrees +/- 8.49 (SD) in the AA4203 group and 3.35 +/- 3.41 degrees in the AcrySof SN60T group (P = .0232). One AcrySof SN60T IOL (1%) and 8 AA4203 IOLs (8.9%) were 15 degrees or more off axis (P = .01). No AcrySof SN60T IOL and 3.3% of AA4203 IOLs required surgical repositioning. Both toric IOLs had good rotational stability and were effective in reducing preexisting corneal astigmatism. Based on the mean axis deviation and the number of IOLs rotating 15 degrees or more, the AcrySof SN60T toric IOL showed statistically better rotational stability.